2013
DOI: 10.1063/1.4792695
|View full text |Cite|
|
Sign up to set email alerts
|

Photocatalytic water splitting to hydrogen production of reduced graphene oxide/SiC under visible light

Abstract: We report a method to realize the H2 production and graphene-oxide (GO) reduction simultaneously over GO/SiC composite under visible light irradiation with KI as sacrifice reagent. The weight content of GO is regulated in the reaction system. The rate of H2 production reaches to 95 μL/h with 1% GO content in GO/SiC composite system, which is 1.3 times larger compared to the case in pure SiC NPs under visible light. The reduced-GO sheet can serve as an electron collector and transporter to efficiently separate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Figure 6(b) shows the high-resolution spectrum of Au 4 f with two pronounced peaks at 83.7 and 87.0 eV, associated with Au 4f 7/2 and Au 4f 5/2 , respectively. This observation is in good agreement with the widely reported XPS spectra of metallic Au° on RGO nanosheets 14,16 . This Au intense peaks indicates that the Au 3+ ions were completely reduced to Au° metallic nanodots on α-Fe 2 O 3 /RGO ternary nanocomposites under sunlight irradiation with chlorophyll.…”
Section: Resultssupporting
confidence: 92%
“…Figure 6(b) shows the high-resolution spectrum of Au 4 f with two pronounced peaks at 83.7 and 87.0 eV, associated with Au 4f 7/2 and Au 4f 5/2 , respectively. This observation is in good agreement with the widely reported XPS spectra of metallic Au° on RGO nanosheets 14,16 . This Au intense peaks indicates that the Au 3+ ions were completely reduced to Au° metallic nanodots on α-Fe 2 O 3 /RGO ternary nanocomposites under sunlight irradiation with chlorophyll.…”
Section: Resultssupporting
confidence: 92%
“…Xiang et al56 demonstrated that the photocatalytic H 2 ‐production rate of the RGO/g‐C 3 N 4 composite exceeded that of the pure g‐C 3 N 4 by more than 3.07 times owing to the efficient separation of the photogenerated electron‐hole pairs and the lengthened lifetime of the charge carriers by incorporation of RGO. Yang et al53 presented a RGO/3C‐SiC photocatalyst with a H 2 ‐production rate of 95 μL h −1 , which was 1.3 times larger than that of the pure 3C‐SiC nanoparticles. Lately, Mou et al57 prepared a novel TiSi 2 /RGO composite using RuO 2 as a cocatalyst to produce H 2 from overall splitting of pure water under visible light irradiation.…”
Section: Graphene As An Electron Acceptor and Transportermentioning
confidence: 99%
“…To explore the composition of our SiC NSs more thoroughly, Raman spectroscopy was adopted to compare the change of specific peaks of rGO structure. As shown in Figure b, two peaks at 792 and 947 cm −1 can be found in the SiC NSs, which correspond to the formation of SiC . All the samples give peaks at 1337 and 1599 cm −1 , which belong to D band and G band of rGO, respectively.…”
Section: Resultsmentioning
confidence: 85%